2016
DOI: 10.1002/2016ef000371
|View full text |Cite
|
Sign up to set email alerts
|

Developing the greatest Blue Economy: Water productivity, fresh water depletion, and virtual water trade in the Great Lakes basin

Abstract: The Great Lakes basin hosts the world's most abundant surface fresh water reserve. Historically an industrial and natural resource powerhouse, the region has suffered economic stagnation in recent decades. Meanwhile, growing water resource scarcity around the world is creating pressure on water-intensive human activities. This situation creates the potential for the Great Lakes region to sustainably utilize its relative water wealth for economic benefit. We combine economic production and trade datasets with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 48 publications
(91 reference statements)
0
22
0
Order By: Relevance
“…Secondly, local government departments should implement the reasonable tiered water price according to the monthly water consumption on the premise of fully considering the total amount of water resources and the level of economic development in different regions [52,57,58,59], so as to raise residents’ awareness of water conservation. Thirdly, while ensuring the export of domestic products, the import of water-intensive products should be appropriately increased to alleviate the pressure of regional water shortage in certain years [53,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, local government departments should implement the reasonable tiered water price according to the monthly water consumption on the premise of fully considering the total amount of water resources and the level of economic development in different regions [52,57,58,59], so as to raise residents’ awareness of water conservation. Thirdly, while ensuring the export of domestic products, the import of water-intensive products should be appropriately increased to alleviate the pressure of regional water shortage in certain years [53,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…(Mayer et al 2016), Yellow River basin (Feng et al 2012), and major aquifers of the US(Marston et al 2015) have been evaluated. These are examples of VWT studies at the watershed scale that provide information at a scale that is meaningful for water resources managers.5.2.…”
mentioning
confidence: 99%
“…Many municipalities withdraw from groundwater stocks and return treated wastewater to surface waters 30 ( Figure 1b). As an example, Mayer et al (2016) found that municipalities and industries in the Great Lakes region have a netnegative consumptive use of in-channel surface water on average (with important exceptions), because on average these users withdraw from groundwater and return to surface waters. Many thermoelectric power plants and industrial users are characterized by large withdrawals from surface water stocks followed by return of lower-quality water (Figure 1c), raising the issue of "grey" water footprints (Hoekstra et al, 2011).…”
Section: Consumptive Water Use Measurement Is Complicatedmentioning
confidence: 99%